Difficulties in diagnosis of tuberculosis without bacteriologic confirmation in a 15-year-old boy from contact with a patient with tuberculosis: A case report - Kostić Gordana; Medović Raša; Marković Slavica; Rašković Zorica; Igrutinović Zoran; Ćupurdija Vojislav; Petrović Marina (Vojnosanitetski Pregled)
Introduction. After the contact with a patient suffering from tuberculosis (TB), previously healthy children have 1%–16% possibility to develop the disease. TB diagnosis in children is not easy to confirm so 15%–25% of cases remain undiagnosed. Case report. A 15-yearold- boy was hospitalized with productive cough, pain in the right flank area, fever, and fatigue, loss of appetite and night sweats. One of the boy's uncles was cured of tuberculosis, another uncle had active tuberculosis and both of them were in contact with the boy, but they did not live in the same household. During the physical examination, the child was febrile, with dyspnea, pale, with profuse sweating, debilitate. BCG (Bacillus Calmette – Guérin) scar was present. The auscultatory findings of the lungs showed quiet breathing from the scapula to the right lung base and chest radiography suggested massive right sided pleuropneumonia. The parameters of the inflammation were high and Mycobacterium tuberculosis (MTB) was not found in the samples of sputum and gastric lavage. Pleural puncture revealed exudative nature in the aspirated fragment. Cytology was nonspecific, the MTB was not found and the planted surfaces on Lowenstein-Jensen remained sterile. Tuberculin skin test (TST) – Mantoux was positive (+ 10 mm), Interferon Gamma Release Assay (QuantiFERON- TB GOLD In-Tube) was negative. The boy was unsuccessfully treated with broad spectrum antibiotics. By video-assisted thoracoscopy, the pleural tissue clip confirmed the benign chronic granulomatous process, while histochemical staining did not show MTB. The treatment with anti-TB medication led to clinical and radiographic recovery. The boy is now in good general condition, without consequences of the disease. Conclusion. This case report pointed out the importance of risk factors and difficulties in diagnosing TB in children.